Anti-frizzy wig hairline and production process thereof

Through the hybrid spinning technology of polyester, polyacrylonitrile and polyurethane, the wig frizz and knotting problems are solved, and the antistatic and matte effects are improved, which extends the service life and improves wear comfort.

CN119121424APending Publication Date: 2024-12-13YIWU FALIBANG HAIR PROD TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411297467.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing wig products are prone to frizz, knotting and electrostatic accumulation during use, which affects the beauty and wear comfort. The antibacterial simulated wig fibers have poor performance in frizz resistance, resulting in the fibers being easily entangled and difficult to untie, and increase care. Difficulty and shorten service life.

Method used

Using mixed spinning technology of polyester fiber, polyacrylonitrile fiber and polyurethane fiber, the smoothness and anti-static properties of the fiber are improved through heat treatment, chemical treatment and tensile treatment, combined with specific fiber fineness and crystallinity to form resistance. Frizzy wigs ensure less friction between the fibers, less easily wrapped, and has a matte finish and high elasticity.

Benefits of technology

Significantly improve the anti-frizz performance of wigs, reduce knotting, improve wear comfort and care convenience, extend the service life of wigs, while maintaining a natural appearance and realistic effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121424A_ABST
    Figure CN119121424A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of wigs, and provides an anti-frizzy wig hairline and a production process thereof.The anti-frizzy wig hairline is formed by evenly mixing and spinning refined source materials, Tanglong filaments and hoglong filaments, the refined source materials account for 30%-40%, the Tanglong filaments account for 25%-35%, and the hoglong filaments account for the rest part except the refined source materials and the Tanglong filaments. The fine source material is composed of polyester fibers, the Tanglong filaments are composed of polyacrylonitrile fibers, and the hoglong filaments are composed of polyurethane fibers. By means of the technical scheme, the problems that wig fibers in the prior art are poor in frizz resistance, wig is prone to being knotted in the using process, the daily nursing difficulty of a user is increased, and when the user tries to unknot, the fibers are prone to being broken or abraded, and the service life of the wig is shortened are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wigs, and in particular to an anti-frizz wig hair and a production process thereof. Background Art

[0002] As an important beauty product, wigs are widely used in hair styling, hair modification and medical aids. The production process of wigs usually includes the selection of fiber raw materials, fiber pretreatment, spinning, dyeing, shaping, and the final wig production. Among these steps, the selection and treatment of fibers is one of the key factors that determine the quality of wigs, which directly affects the appearance, feel, durability and wearing comfort of wigs.

[0003] Existing wig products are usually made of synthetic or natural fibers, and after fine processing, they can imitate the appearance and texture of human hair. However, due to the physical properties of wig fibers and the limitations of production processes, wigs are prone to frizz, tangles, static electricity accumulation and other problems in daily use. These problems not only affect the beauty of the wig, but also increase the daily care burden of the user.

[0004] An antibacterial simulated wig fiber in an existing patent successfully endows the wig with good antibacterial properties by adding antibacterial materials such as modified eggshell powder, modified beeswax, and nano zinc oxide, thereby enhancing the hygiene and safety of the wig. However, this antibacterial simulated wig fiber performs poorly in terms of anti-frizziness. Due to the limitations of the fiber structure and surface characteristics, the wig is prone to fiber knotting and entanglement during use, forming knots that are difficult to untie. This not only seriously affects the appearance of the wig, making it look unnatural, but also increases the difficulty of users in daily care. When trying to untie these knots, the wig fibers are easily damaged, resulting in fiber breakage or wear, which in turn shortens the service life of the wig. Summary of the invention

[0005] The present invention provides an anti-frizz wig hair which can significantly improve the anti-frizz performance of the wig and a production process thereof, which can not only maintain the beauty and comfort of the wig, but also extend the service life of the wig and reduce the burden of daily care.

[0006] The technical solution of the present invention is as follows: An anti-frizz wig hair is made by spinning after evenly mixing fine material, Tanglong silk and Henglong silk, wherein the fine material accounts for 30%-40%, the Tanglong silk accounts for 25%-35%, and the Henglong silk accounts for the rest of the total proportion after deducting the fine material and Tanglong silk proportions. The fine material is composed of polyester fiber, the Tanglong silk is composed of polyacrylonitrile fiber, and the Henglong silk is composed of polyurethane fiber.

[0007] Furthermore, the refined raw material is polyester fiber with a fiber fineness of 1.5-2.5 dtex, the Tanglong silk is polyacrylonitrile fiber with a fiber fineness of 0.8-1.5 dtex, and the Henglong silk is polyurethane fiber with a fiber fineness of 1.2-2 dtex.

[0008] Furthermore, the refined raw material is polyester fiber with a crystallinity of 30%-40%.

[0009] A production process for anti-frizz wig hair, comprising the following process steps: S1. Select raw materials, such as polyester fiber, polyacrylonitrile fiber and polyurethane fiber; S2, fiber pretreatment, heat treatment and chemical treatment of polyester fiber, surface oxidation treatment, stretching treatment and heat setting treatment of polyacrylonitrile fiber, stretching treatment and cooling setting treatment of polyurethane fiber; S3, fiber cutting, using a fiber cutting machine to cut the pre-treated polyester fiber, polyacrylonitrile fiber, and polyurethane fiber to reduce the fiber length; S4, fiber mixing, uniformly mixing the polyester fiber, polyacrylonitrile fiber, and polyurethane fiber by a mixer or a stirrer; S5, spinning, spinning the mixed fibers of polyester fiber, polyacrylonitrile fiber and polyurethane fiber by melt spinning process; S6, post-processing, heat setting the composite fiber after spinning.

[0010] Further, in step S2, the temperature of the polyester fiber heat treatment is 90°C-110°C, the time of the polyester fiber heat treatment is 30-60 minutes, the treatment liquid of the polyester fiber chemical treatment is a silicone oil emulsion with a concentration of 0.5%-1%, the time of the polyester fiber chemical treatment is 15-30 minutes, the stretching ratio of the polyacrylonitrile fiber stretching treatment is 3:1-5:1, the oxidant of the polyacrylonitrile fiber surface oxidation treatment is a hydrogen peroxide solution with a concentration of 1%-5%, the treatment temperature is 60°C-70°C, the treatment time is 10-20 minutes, and the polyacrylonitrile fiber The temperature of the stretching treatment is 60℃-80℃, the stretching time of the polyacrylonitrile fiber is 10-20 minutes, the temperature of the heat setting of the polyacrylonitrile fiber is 120℃-150℃, the heat setting time of the polyacrylonitrile fiber is 20-30 minutes, the stretching ratio of the polyurethane fiber stretching treatment is 2:1-4:1, the temperature of the polyurethane fiber stretching treatment is 80℃-100℃, the stretching time of the polyurethane fiber is 10-15 minutes, the temperature of the polyurethane fiber cooling and setting is -10℃-0℃, and the cooling and setting time of the polyurethane fiber is 15-30 minutes.

[0011] Furthermore, in step S3, the fiber cutting length is 5-10 mm, and after the fiber cutting is completed, static electricity is eliminated by a static electricity elimination device.

[0012] Further, the spinning steps in step S5 are as follows: S510, heating, heating the mixed fiber to 220° C.-240° C. through an extruder, and adding a matte agent and an antistatic agent to the fiber while heating; S520, extruding, extruding the heated mixed fiber into fiber filaments, the nozzle aperture of the extruder is 0.2-0.5 mm; S530, cooling, cooling and solidifying the fiber filaments, the cooling temperature is 20°C-30°C; S540, stretching, stretching the cooled fiber filaments, with a stretching ratio of 3:1-5:1, a stretching temperature of 80°C-110°C, and a stretching rate of 500-1500 m / min.

[0013] Furthermore, in step S6, the heat setting temperature is 150° C.-180° C., and the heat setting time is 20-30 minutes.

[0014] The working principle and beneficial effects of the present invention are: The present invention effectively reduces the friction and entanglement problems between wig fibers through the smoothness and antistatic properties of polyester fibers, avoids the occurrence of knots, improves the performance of wigs in daily wear, and makes them easier to comb and maintain. The matte effect of polyacrylonitrile fibers makes the wig look closer to natural hair quality, avoiding the unreality caused by bright reflection. Polyacrylonitrile fibers also make the wigs less likely to age or deform during use, maintaining long-term beauty. The high elasticity and shaping ability of polyurethane fibers ensure that the wig can maintain a stable shape during wearing, and will not easily collapse or deform due to changes in the environment or wearing time, greatly extending the service life of the wig, while reducing the difficulty of daily care for the wearer. By mixing these three fibers in a specific proportion, the wig hair can have the advantages of smoothness, natural beauty and long-lasting shaping, thereby effectively solving the problems of poor anti-frizziness, easy knotting and entanglement, and difficult care of wigs in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0016] Figure 1 It is a flow chart of the production process of the present invention. DETAILED DESCRIPTION

[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] like Figure 1 As shown, this embodiment proposes an anti-frizz wig hair, which is made by spinning after evenly mixing fine source material, Tanglong silk and Henglong silk, wherein the fine source material accounts for 30%-40%, the Tanglong silk accounts for 25%-35%, and the Henglong silk accounts for the rest of the total proportion after deducting the fine source material proportion and the Tanglong silk proportion. The fine source material is composed of polyester fiber, the Tanglong silk is composed of polyacrylonitrile fiber, and the Henglong silk is composed of polyurethane fiber.

[0019] The main function of the polyester fiber in the wig hair is to provide smoothness and anti-frizz performance. Its surface is smooth and the friction coefficient is low, so that the fibers are not easy to generate static electricity and frizz when rubbing against each other; at the same time, it also has high mechanical strength and wear resistance, which helps the durability of the wig hair and maintains a smooth effect for a long time. The proportion of 30%-40% of the fine material can ensure that the surface of the wig is smooth, easy to comb, and not easy to tangle. In the range of 30%-40%, when the proportion of the fine material is in the range of 30%-35%, the wig can maintain good smoothness, significant anti-frizz effect, and will not appear too shiny, and can maintain a natural appearance; when the proportion of the fine material is in the range of 35%-40%, the wig will further improve the smoothness, but it may make the wig appear too smooth, thus affecting a certain sense of naturalness. At the same time, if the fine material accounts for more than 40%, the surface of the wig will be too smooth, lacking natural texture, affecting the overall appearance; if the fine material accounts for less than 30%, the wig will be insufficiently smooth and anti-frizzy, and the wig will be easily knotted and frizzy. Preferably, the fine material accounts for 34%. Under this ratio, the smoothness and anti-frizziness of the fine material are well balanced. This ratio can provide sufficient surface smoothness and reduce knotting, while not appearing too shiny, maintaining the natural appearance of the wig.

[0020] The main function of Tanglong silk composed of polyacrylonitrile fiber in wig hair is to give the wig hair a matte effect, making the wig look more natural and non-reflective, thereby improving the realism of the wig; at the same time, it also has certain chemical resistance and UV resistance, which enhances the durability of the wig in daily use. Tanglong silk with a proportion between 25% and 35% will give the wig a matte effect, making it more realistic and natural under various lighting conditions, and will not appear unreal due to reflection. In the range of 25%-35%, when the proportion of Tanglong silk is in the range of 25%-30%, the wig has a moderate matte effect while maintaining a certain softness and natural touch; when the proportion of Tanglong silk is in the range of 30%-35%, it will further enhance the matte effect of the wig, making the wig non-reflective under strong light and appear more natural. At the same time, if the proportion of Tanglong silk exceeds 35%, the matte effect will be too strong, the touch of the wig will become dry, and the softness and comfort will be affected; if the proportion of Tanglong silk is less than 25%, the matte effect will be insufficient, and the wig may appear too shiny under light and lose its realism. Preferably, the proportion of Tanglong silk is 33%. This ratio can ensure the matte effect of the wig while maintaining good softness and natural touch. This ratio can make the wig appear more realistic and natural under various lighting conditions.

[0021] Henglong silk composed of polyurethane fibers mainly provides elasticity and shaping functions in wig hair. Its high elastic modulus allows the wig to quickly return to its original shape after being stressed and maintain a good hairstyle. At the same time, it also has a certain degree of adhesion, which helps the wig hair maintain its overall shape and consistency during the production process. Preferably, the proportion of Henglong silk is 33%. This ratio can provide sufficient shaping ability for the wig, keep the hairstyle from collapsing, and does not affect the characteristics of other fibers, such as smoothness and matte effect.

[0022] In this embodiment, the refined raw material is polyester fiber with a fiber fineness of 1.5-2.5 dtex, the Tanglong silk is polyacrylonitrile fiber with a fiber fineness of 0.8-1.5 dtex, and the Henglong silk is polyurethane fiber with a fiber fineness of 1.2-2 dtex.

[0023] Polyester fiber with a fiber fineness of 1.5-2.5dtex can provide a good feel and smoothness, reduce the frizziness of the wig, and improve wearing comfort; if the fiber fineness of the polyester fiber exceeds 2.5dtex, the wig will appear rough, not smooth, and increase the possibility of frizziness and knotting; if the fiber fineness of the polyester fiber is less than 1.5dtex, the strength and wear resistance of the fiber will be reduced, the risk of wig breakage during use will be increased, and the glossiness and overall appearance of the wig will be affected. Polyacrylonitrile fiber with a fiber fineness of 0.8-1.5dtex can provide a more natural matte effect and a texture close to real hair, improving the realism of the wig; if the fiber fineness of the polyacrylonitrile fiber exceeds 1.5dtex, the wig will appear unnatural and the glossiness will be too high, affecting the realistic effect; if the fiber fineness of the polyacrylonitrile fiber is less than 0.8dtex, the fiber strength will be insufficient, affecting the durability and mechanical strength of the wig, and it is not suitable for the matte effect. Polyurethane fibers with a fiber fineness of 1.2-2dtex have good elasticity and flexibility while maintaining sufficient strength, which is suitable for styling effects; if the fiber fineness of the polyurethane fiber exceeds 2dtex, it will affect the flexibility and comfort of the fiber, increase the weight of the wig, and affect the wearing experience; if the fiber fineness of the polyurethane fiber is lower than 1.2dtex, it will reduce the elasticity and strength of the fiber, affecting the styling effect and durability of the wig.

[0024] Preferably, the fiber fineness of polyester fiber is 2dtex, and the fiber fineness of 2dtex can provide good hand feeling and smoothness, making the touch of wig closer to natural hair quality, and at the same time, this fineness ensures that the fiber has sufficient strength and durability, while maintaining a comfortable wearing feeling and reducing the possibility of knotting. The fiber fineness of polyacrylonitrile fiber is 1.2dtex, and the fineness of 1.2dtex can provide a natural matte effect, close to the texture of real hair, and enhance the realism of wig. At the same time, this fineness ensures that the fiber can provide good hand feeling and glossiness while maintaining sufficient strength. The fiber fineness of polyurethane fiber is 1.5dtex, and the fiber fineness of 1.5dtex can ensure that the fiber has good elasticity and shaping ability, which is suitable for maintaining the shape and hairstyle of wig. At the same time, this fineness balances elasticity and strength, ensuring that the wig has good recovery and comfort during use.

[0025] In this embodiment, the refined raw material is polyester fiber with a crystallinity of 30%-40%.

[0026] Polyester fibers with a crystallinity of 30%-40% help improve the smoothness and wrinkle resistance of the fibers while maintaining a certain degree of flexibility to ensure that the wig is natural and realistic; if the crystallinity of the polyester fibers exceeds 40%, the flexibility of the fibers will decrease, making the wig too stiff, affecting the wearing comfort and appearance; if the crystallinity of the polyester fibers is lower than 30%, the fibers will become wrinkled and frizzy, affecting the smoothness and natural appearance of the wig.

[0027] Preferably, the crystallinity of the polyester fiber is 35%. 35% crystallinity helps to improve the smoothness of the fiber, reduce wrinkles and frizz, while maintaining a certain flexibility. At the same time, this crystallinity ensures the stability of the fiber in subsequent processing and use, and improves the overall quality and service life of the wig.

[0028] like Figure 1 As shown, this embodiment proposes a production process for anti-frizz wig hair, including the following process steps: S1. Select raw materials, select polyester fiber with a crystallinity of 35% and a fiber fineness of 2 dtex, select polyacrylonitrile fiber with a fiber fineness of 1.2 dtex, and select polyurethane fiber with a fiber fineness of 1.5 dtex.

[0029] S2. Fiber pretreatment: thermal and chemical treatment of polyester fiber to improve its smoothness and anti-frizziness, surface oxidation treatment, stretching treatment and heat setting treatment of polyacrylonitrile fiber to improve its matte effect and touch, stretching treatment and cooling setting treatment of polyurethane fiber to enhance its elasticity and shape memory function.

[0030] S3, fiber cutting, using a fiber cutting machine to reduce the fiber length of the pre-treated polyester fiber, polyacrylonitrile fiber, and polyurethane fiber, and cut the long fiber into short fiber segments to ensure uniform mixing and smooth spinning.

[0031] S4, fiber mixing, the polyester fiber, polyacrylonitrile fiber and polyurethane fiber are uniformly mixed by a mixer or agitator.

[0032] S5. Spinning: Spinning a mixture of polyester fiber, polyacrylonitrile fiber and polyurethane fiber by melt spinning process.

[0033] S6, post-processing, heat setting the composite fiber after spinning to ensure the final shape and stability of the wig.

[0034] In step S2, the temperature of the heat treatment of the polyester fiber is 90°C-110°C. If the heat treatment temperature exceeds 110°C, the fiber structure will be damaged or the physical properties will be reduced, such as increased brittleness or reduced strength. If the heat treatment temperature is lower than 90°C, the heat treatment effect will be insufficient, and the smoothness and anti-frizziness of the fiber will be limited, and the expected quality requirements cannot be met. The preferred heat treatment temperature of the polyester fiber is 100°C, which is the optimal temperature for the heat treatment of polyester fiber. At this temperature, the surface friction coefficient of the fiber can be significantly reduced, thereby improving the smoothness, and can effectively eliminate frizz, and this temperature will not cause thermal damage to the fiber, ensuring that its physical properties remain stable. The heat treatment time of the polyester fiber is 30-60 minutes. If the heat treatment time exceeds 60 minutes, the fiber will be over-treated, and the flexibility and durability of the fiber may be adversely affected; if the heat treatment time is less than 30 minutes, the heat treatment will be insufficient, and the surface friction coefficient of the fiber cannot be effectively reduced. Preferably, the heat treatment time of polyester fiber is 45 minutes. The treatment time of 45 minutes is sufficient to allow the fiber to be evenly heated to achieve the expected physical property optimization effect, and will not cause over-treatment or changes in fiber structure. The treatment liquid for chemical treatment of polyester fiber is a silicone oil emulsion with a concentration of 0.5%-1% (silicone oil emulsion is mainly composed of silicone oil, emulsifier, and water, and the concentration of silicone oil emulsion refers to the mass percentage of silicone oil in the emulsion). If the concentration of silicone oil emulsion exceeds 1%, it will cause the silicone oil to form an overly thick film on the fiber surface, and the wig hair will appear too shiny and unnatural, and it may also affect the air permeability of the fiber; if the concentration of silicone oil emulsion is lower than 0.5%, the lubricating effect of silicone oil emulsion will be insufficient, and the anti-frizziness and smoothness of the fiber will be limited. Preferably, the concentration of silicone oil emulsion is 0.8%. The concentration of 0.8% provides sufficient lubricity to form a uniform silicone oil film on the fiber surface, and will not excessively increase the weight of the fiber or affect its air permeability. The chemical treatment time of polyester fiber is 15-30 minutes. If the chemical treatment time exceeds 30 minutes, the silicone oil will accumulate excessively on the fiber surface, and the wig hair will be too smooth or greasy. If the chemical treatment time is less than 15 minutes, the silicone oil will not be able to fully penetrate the fiber surface, and the lubrication effect will be uneven. Preferably, the chemical treatment time is 20 minutes. The 20-minute soaking time allows the silicone oil to fully penetrate the fiber surface and form a stable lubricating film, while avoiding excessive soaking that causes the fiber surface to be sticky or affects subsequent processing.

[0035] The oxidant for the surface oxidation treatment of polyacrylonitrile fiber is a hydrogen peroxide solution with a concentration of 1%-5%. The hydrogen peroxide solution with a concentration of 1%-5% can ensure effective oxidation while also better protecting the wig fiber, avoiding excessive oxidation to cause the fiber to lose strength and become brittle on the surface; if the concentration is lower than 1%, the oxidation effect will be insufficient, the fiber surface modification will not be significant, and the antibacterial and hydrophilic effects will be poor; if the concentration exceeds 5%, the fiber surface will be over-oxidized, thereby damaging the mechanical properties of the fiber, such as strength loss, easy brittle cracking, etc.; preferably, the concentration of the hydrogen peroxide solution is 3%, which can effectively achieve surface oxidation of the fiber, so that the fiber has good hydrophilicity, while avoiding excessive weakening of the fiber strength due to high concentration. The treatment temperature is 60℃-70℃. The temperature range of 60℃-70℃ can effectively control the temperature effect on the wig fiber while improving the oxidation effect, avoiding a significant decrease in fiber strength and other adverse changes; if the treatment temperature is lower than 60℃, the oxidation reaction rate will be reduced, the treatment effect will be unsatisfactory, and the fiber modification will be insufficient; if the treatment temperature exceeds 70℃, the decomposition rate of hydrogen peroxide will be too fast, resulting in excessive oxidation or damage to the fiber surface; the preferred treatment temperature is 65℃, which can accelerate the decomposition and oxidation reaction of hydrogen peroxide, ensuring sufficient treatment of the fiber surface without excessively damaging the fiber structure. The treatment time is 10-20 minutes. The time range of 10-20 minutes can ensure the uniformity and depth of the treatment without causing excessive damage to the fiber. If the treatment time is less than 10 minutes, the oxidation reaction will be incomplete and the fiber surface modification effect will be poor. If the treatment time exceeds 20 minutes, excessive oxidation will occur, resulting in decreased fiber performance and problems such as brittleness and hardening of the surface. Preferably, the treatment time is 15 minutes, which is enough time for hydrogen peroxide to fully react with the fiber surface and complete the oxidation treatment without exposing the fiber to the oxidant for too long, thereby protecting its internal structure.

[0036] The steps of surface oxidation treatment of polyacrylonitrile fiber are preparing hydrogen peroxide solution, heating hydrogen peroxide solution, immersing polyacrylonitrile fiber in hydrogen peroxide solution, quickly rinsing the treated polyacrylonitrile fiber with cold water, and drying the rinsed fiber.

[0037] The stretching ratio of the polyacrylonitrile fiber stretching treatment is 3:1-5:1. If the stretching ratio is greater than 5:1, the fiber will become too rigid. Although the strength is improved, the flexibility will be significantly reduced, which is easy to cause breakage; if the stretching ratio is less than 3:1, the orientation and crystallinity of the fiber will not be improved enough, and the expected matte effect cannot be achieved, and the surface touch will be poor. Preferably, the stretching ratio of the polyacrylonitrile fiber stretching treatment is 4:1. The stretching ratio of 4:1 can effectively improve the crystallinity and molecular orientation of the fiber, thereby enhancing the matte effect and the surface touch of the fiber. The temperature of the polyacrylonitrile fiber stretching treatment is 60℃-80℃. If the temperature of the stretching treatment exceeds 80℃, the fiber will be stretched unevenly due to excessive softening, and there may even be problems with fiber breakage or structural damage; if the temperature of the stretching treatment is lower than 60℃, the fiber will harden during stretching, affecting the stretching effect, and the flexibility and surface smoothness of the fiber may not be effectively improved. Preferably, the temperature of the polyacrylonitrile fiber stretching treatment is 70°C. The temperature of 70°C can keep the fiber flexible enough during stretching, avoid breakage or damage during the stretching process, and ensure that the crystallinity and orientation of the fiber are appropriately improved. The stretching time of the polyacrylonitrile fiber is 10-20 minutes. If the stretching time exceeds 20 minutes, the fiber will be over-stretched, the fiber structure will be loose or broken, and the subsequent processing and performance will be affected; if the stretching time is less than 10 minutes, the stretching effect will be insufficient, the molecular orientation and crystallinity of the fiber will be limited, and the matte effect cannot achieve the best. Preferably, the stretching treatment time of the polyacrylonitrile fiber is 15 minutes. The 15-minute stretching time allows the fiber to be evenly stressed and ensures that the internal structure of the fiber is fully adjusted, further improving the performance of the fiber. The heat setting temperature of polyacrylonitrile fiber is 120℃-150℃. If the heat setting temperature exceeds 150℃, the fiber will be overheated, resulting in structural damage, the fiber will become fragile, and even scorching or discoloration will occur; if the heat setting temperature is lower than 120℃, the heat setting effect of the fiber will be insufficient, resulting in the fiber shrinking or deforming after cooling, affecting the final quality of the wig. Preferably, the heat setting temperature of polyacrylonitrile fiber is 135℃. The temperature of 135℃ can effectively fix the stretched fiber structure, prevent the fiber from shrinking and maintain its matte effect and surface touch. The heat setting time of polyacrylonitrile fiber is 20-30 minutes. If the heat setting time exceeds 30 minutes, the fiber will cause performance degradation due to long-term high temperature treatment, and even aging will occur, affecting the service life of the fiber; if the heat setting time is less than 20 minutes, the heat setting effect will be insufficient, the dimensional stability and appearance of the fiber cannot be effectively maintained, and the fiber is easily deformed. Preferably, the heat setting time of the polyacrylonitrile fiber is 25 minutes, which is sufficient to allow the fiber to be completely stable during the heat setting process, thereby ensuring that the physical properties and appearance characteristics of the fiber are maintained.

[0038] The stretching ratio of polyurethane fiber stretching treatment is 2:1-4:1. If the stretching ratio exceeds 4:1, the fiber will be overstretched, the molecular chain will be overextended, the fiber will be easily broken, and the elasticity and durability will be negatively affected; if the stretching ratio is lower than 2:1, the molecular chain arrangement effect of the fiber will be limited, the elasticity will not be improved enough, and the shape memory ability may not meet expectations. Preferably, the stretching ratio is 3:1. The stretching ratio of 3:1 can provide moderate tension, promote the orderly arrangement of the molecular chains, and improve the elasticity and shaping ability of the fiber. This ratio avoids the risk of excessive deformation or breakage of the fiber while ensuring elasticity. The temperature of polyurethane fiber stretching treatment is 80℃-100℃. If the stretching temperature exceeds 100℃, the fiber will be oversoftened or even melted, the molecular chain will break, and the elasticity and strength of the fiber will be seriously affected; if the stretching temperature is lower than 80℃, the softening effect of the polyurethane fiber will be insufficient, uneven deformation will occur during the stretching process, and the expected elasticity and shaping effect cannot be achieved. Preferably, the stretching temperature of the polyacrylonitrile fiber is 90°C. The temperature of 90°C can effectively soften the polyurethane fiber, so that its molecular chain is evenly stressed during the stretching process, while maintaining sufficient elasticity and shape memory function. This temperature can not only avoid damage to the fiber structure, but also improve the physical properties of the fiber. The stretching treatment time of the polyurethane fiber is 10-15 minutes. If the stretching time exceeds 15 minutes, the fiber will age due to long-term high-temperature treatment, its elasticity will decrease, and its shape memory ability will weaken; if the stretching time is less than 10 minutes, the stretching treatment time will be insufficient, the molecular chain arrangement of the fiber will not be sufficient, and the shape memory ability will not be ideal. Preferably, the stretching treatment time is 12 minutes. The 12-minute treatment time can ensure that the fiber is fully heated and completes the reorganization of the molecular chain, further enhancing its shape memory ability, while avoiding the degradation of fiber performance caused by excessive treatment. The cooling and setting temperature of polyurethane fiber is -10℃-0℃. If the cooling and setting temperature exceeds 0℃, the cooling process will not be fast enough, the fiber's morphology and structure cannot be effectively fixed, and the shape memory ability will decrease; if the cooling and setting temperature is lower than -10℃, the cooling process will be too intense, and the fiber's molecular chain will become brittle or internal stress will be uneven due to rapid cooling, affecting the elasticity and strength of the fiber. Preferably, the cooling and setting temperature of polyurethane fiber is -5℃. The cooling temperature of -5℃ can quickly stabilize the fiber after high-temperature stretching, fix its molecular chain structure, and thus enhance the shape memory effect. This temperature can avoid the fiber from having uneven structure due to too fast or too slow cooling. The cooling and setting time of polyurethane fiber is 15-30 minutes. If the cooling and setting time exceeds 30 minutes, the fiber will become brittle due to being in a low temperature environment for a long time, affecting its flexibility and durability; if the cooling and setting time is lower than 15 minutes, the cooling time will be insufficient, and the fiber's morphology and structure cannot be completely stabilized, resulting in deformation in subsequent use.Preferably, the cooling and shaping time of the polyurethane fiber is 20 minutes. The 20-minute cooling time can ensure that the morphology and structure of the fiber are completely stable, further improve its shape memory and elasticity retention capabilities, and avoid excessive cooling that causes fiber embrittlement.

[0039] In step S3, the fiber cutting length is 5-10 mm, which is suitable for the working principle of the mixer or agitator, and ensures that the fibers can be evenly distributed during mixing, and there will be no blockage or unevenness during the spinning process. After the fibers are cut, they are electrostatically eliminated by an electrostatic eliminator to prevent the fibers from sticking together during mixing and affecting uniformity.

[0040] The spinning steps in step S5 are as follows: S510, heating, the mixed fiber is heated to 220℃-240℃ through an extruder to ensure that the material is completely melted without decomposition, and matte agent and antistatic agent are added to the fiber while heating. The matte agent is titanium dioxide, and the addition ratio of titanium dioxide is 0.5%-2% (relative to the total weight of the fiber raw material) to improve the surface gloss of the fiber and make it more natural and realistic. The antistatic agent is quaternary ammonium salt, and the addition ratio of quaternary ammonium salt is 0.1%-0.5% (relative to the total weight of the fiber raw material) to reduce the static electricity accumulation of the fiber during use.

[0041] If the heating temperature exceeds 240°C, the material will decompose or degrade, affecting the mechanical properties and appearance of the fiber; if the heating temperature is lower than 220°C, it will lead to incomplete melting, high viscosity of the material, difficulty in extrusion, and poor fiber molding. The preferred heating temperature is 230°C, which is a suitable temperature for polyester fiber, polyacrylonitrile fiber, polyurethane fiber, etc. in the melt spinning process, which can ensure that all components are evenly melted without decomposition, which is conducive to extrusion and molding during the spinning process. If the addition ratio of titanium dioxide exceeds 2%, it will cause uneven dispersion of titanium dioxide in the fiber, increase the resistance during melt extrusion, and even affect the mechanical properties of the fiber, causing processing difficulties or fiber embrittlement; if the addition ratio of titanium dioxide is lower than 0.5%, it will lead to insufficient matte effect, and the fiber surface will still appear relatively bright, and the desired realistic effect cannot be achieved. Preferably, the addition ratio of titanium dioxide is 1%, and 1% of titanium dioxide can effectively provide a matte effect, so that the fiber has a natural gloss, and it will not appear too smooth or reflective, thereby increasing the realism of the wig. If the proportion of quaternary ammonium salt added exceeds 0.5%, it will lead to excessive accumulation of antistatic agents in the fibers, thereby affecting the feel and appearance of the fibers and possibly increasing production costs; if the proportion of quaternary ammonium salt added is lower than 0.1%, the antistatic effect will not be significant enough, and the fibers will still easily accumulate static electricity, affecting the user experience.

[0042] S520, extruding, extruding the heated mixed fiber into fiber filaments, the nozzle aperture of the extruder is 0.2-0.5 mm.

[0043] If the nozzle aperture exceeds 0.5mm, the extruded fiber will be too large, the product will appear too rough and lack naturalness; if the nozzle aperture is less than 0.2mm, the extrusion pressure will be too high, the fiber will be easily broken or poorly formed. Preferably, the nozzle aperture is 0.3mm, which can produce fibers of moderate fineness, ensuring fiber strength while maintaining softness and simulation effect.

[0044] S530, cooling, rapid cooling and solidification through cooling medium (air), the cooling temperature is 20℃-30℃ (room temperature).

[0045] S540, stretching, stretching the cooled fiber filaments, with a stretching ratio of 3:1-5:1, a stretching temperature of 80°C-110°C, and a stretching rate of 500-1500m / min to ensure the strength and elasticity of the fiber.

[0046] If the stretching ratio exceeds 5:1, the fiber will be overstretched, which will lead to fiber breakage or insufficient elasticity; if the stretching ratio is lower than 3:1, the fiber will be understretched, and the strength and elasticity will be insufficient. Preferably, the stretching ratio is 4:1. The stretching ratio of 4:1 can stretch the fiber to the required fineness without sacrificing fiber strength, while giving the fiber good elasticity and flexibility. If the stretching temperature exceeds 110°C, the fiber will soften or flow, which will lead to difficulty in stretching; if the stretching temperature is lower than 80°C, the fiber crystallinity will be insufficient, and the strength and heat resistance will decrease. Preferably, the stretching temperature is 90°C, and the temperature of 90°C helps the fiber to obtain the ideal crystallinity during the stretching process, ensuring the mechanical properties of the fiber. If the stretching rate exceeds 1500m / min, the fiber will be overstretched and easy to break; if the stretching rate is lower than 500m / min, the fiber will be unevenly stretched and insufficient in strength. Preferably, the stretching rate is 1000m / min, at which the fiber can obtain uniform stretching to ensure mechanical properties and dimensional stability.

[0047] In step S6, the heat setting temperature is 150°C-180°C, and the heat setting time is 20-30 minutes to ensure the dimensional stability and shape memory effect of the fiber. If the heat setting temperature exceeds 180°C, it will cause excessive shrinkage or damage to the fiber; if the heat setting temperature is lower than 150°C, it will lead to poor setting effect and deformation of the fiber during use. Preferably, the heat setting temperature is 170°C, and the temperature of 170°C can form a stable molecular structure inside the fiber to ensure dimensional stability and shape memory effect. If the heat setting time exceeds 30 minutes, the fiber will be over-heat treated, affecting strength and flexibility; if the heat setting time is less than 20 minutes, the fiber will be insufficiently set and the shape will be unstable. Preferably, the heat setting temperature is 25 minutes, and 25 minutes is enough to complete the rearrangement and stabilization of the molecular structure to ensure the setting effect of the fiber.

[0048] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An anti-frizz wig hair, characterized in that: It is made by evenly mixing refined material, Tanglong silk and Henglong silk and then spinning them, wherein the refined material accounts for 30%-40%, the Tanglong silk accounts for 25%-35%, and the Henglong silk accounts for the rest of the total proportion after deducting the refined material and Tanglong silk. The refined material is composed of polyester fiber, the Tanglong silk is composed of polyacrylonitrile fiber, and the Henglong silk is composed of polyurethane fiber.

2. The anti-frizz wig hair according to claim 1, characterized in that: The refined raw material is polyester fiber with a fiber fineness of 1.5-2.5 dtex, the Tanglong silk is polyacrylonitrile fiber with a fiber fineness of 0.8-1.5 dtex, and the Henglong silk is polyurethane fiber with a fiber fineness of 1.2-2 dtex.

3. The anti-frizz wig hair according to claim 1, characterized in that: The refined raw material is polyester fiber with a crystallinity of 30%-40%.

4. A production process for anti-frizz wig hair according to any one of claims 1 to 3, characterized in that: The process steps include: S1. Select raw materials, such as polyester fiber, polyacrylonitrile fiber and polyurethane fiber; S2, fiber pretreatment, heat treatment and chemical treatment of polyester fiber, surface oxidation treatment, stretching treatment and heat setting treatment of polyacrylonitrile fiber, stretching treatment and cooling setting treatment of polyurethane fiber; S3, fiber cutting, using a fiber cutting machine to cut the pre-treated polyester fiber, polyacrylonitrile fiber, and polyurethane fiber to reduce the fiber length; S4, fiber mixing, uniformly mixing the polyester fiber, polyacrylonitrile fiber, and polyurethane fiber by a mixer or a stirrer; S5, spinning, spinning the mixed fibers of polyester fiber, polyacrylonitrile fiber and polyurethane fiber by melt spinning process; S6, post-processing, heat setting the composite fiber after spinning.

5. The production process of anti-frizz wig hair according to claim 4, characterized in that: In step S2, the temperature of the polyester fiber heat treatment is 90°C-110°C, the time of the polyester fiber heat treatment is 30-60 minutes, the treatment liquid of the polyester fiber chemical treatment is a silicone oil emulsion with a concentration of 0.5%-1%, the time of the polyester fiber chemical treatment is 15-30 minutes, the stretching ratio of the polyacrylonitrile fiber stretching treatment is 3:1-5:1, the oxidant of the polyacrylonitrile fiber surface oxidation treatment is a hydrogen peroxide solution with a concentration of 1%-5%, the treatment temperature is 60°C-70°C, the treatment time is 10-20 minutes, and the polyacrylonitrile fiber stretching treatment is 1:1-5:

1. The treatment temperature is 60℃-80℃, the stretching time of polyacrylonitrile fiber is 10-20 minutes, the heat setting temperature of polyacrylonitrile fiber is 120℃-150℃, the heat setting time of polyacrylonitrile fiber is 20-30 minutes, the stretching ratio of polyurethane fiber stretching treatment is 2:1-4:1, the stretching temperature of polyurethane fiber is 80℃-100℃, the stretching time of polyurethane fiber is 10-15 minutes, the cooling and setting temperature of polyurethane fiber is -10℃-0℃, and the cooling and setting time of polyurethane fiber is 15-30 minutes.

6. The production process of anti-frizz wig hair according to claim 4, characterized in that: In step S3, the fiber is cut into a length of 5-10 mm, and after the fiber is cut, it is subjected to static elimination by a static elimination device.

7. The production process of anti-frizz wig hair according to claim 4, characterized in that: The spinning steps in step S5 are as follows: S510, heating, heating the mixed fiber to 220° C.-240° C. through an extruder, and adding a matte agent and an antistatic agent to the fiber while heating; S520, extruding, extruding the heated mixed fiber into fiber filaments, the nozzle aperture of the extruder is 0.2-0.5 mm; S530, cooling, cooling and solidifying the fiber filaments, the cooling temperature is 20°C-30°C; S540, stretching, stretching the cooled fiber filaments, with a stretching ratio of 3:1-5:1, a stretching temperature of 80°C-110°C, and a stretching rate of 500-1500 m / min.

8. The production process of anti-frizz wig hair according to claim 4, characterized in that: In step S6, the heat setting temperature is 150° C.-180° C., and the heat setting time is 20-30 minutes.